Correlation Between Bands Structure and Quantum Magneto Transport Properties in InAs/GaxIn1−xSb Type II Superlattice for Infrared Detection - Benchtaber, Nassima; Nafidi, Abdelhakim; Barkissy, Driss; Boutramine, Abderrezak; Benaadad, Merieme; Melkoud, Samir; Es-Salhi, Es-Said; Chibane, Fatiha (Frontiers in Physics, 2020)
We have used the envelope function formalism to investigate the bands structure of LWIR type II SL InAs (d1 = 2. 18d2)/In0.25Ga0.75Sb(d2 = 21.5 Å). Thus, we extracted optical and transport parameters as the band gap, cut off wavelength, carriers effective mass, Fermi level and the density of state. Our results show that the higher optical cut-off wavelength can be achieved with smaller layer thicknesses. The semiconductor-semi metal transition was studied as a function of temperature. Our results permit us the interpretations of Hall and Shubnikov-de Haas effects. These results are in agreement with experimental results in literature and a guide for engineering infrared detectors.